Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.diii.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of transcatheter embolization of visceral artery pseudoaneurysms using N-butyl cyanoacrylate (NBCA)

Abstract: Transcatheter embolization using NBCA for the treatment of visceral pseudoaneurysms is a safe, effective, and low-cost treatment method with a high success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 20 publications
3
32
0
Order By: Relevance
“…The present study had a technical success rate and clinical success rate of 100% for transcatheter embolization using NBCA as was seen by Izaki et al, ( n = 12),[3] Madhusudhan et al, ( n = 31),[6] Won et al, ( n = 10)[14] in their studies on use of NBCA for embolization of visceral artery pseudoaneurysms. Song et al,[2] reported 92.3% (12 of 13 patients) technical success rate for transcatheter embolization of GI arterial, splenic artery, and hepatic arterial pseudoaneurysms using NBCA.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The present study had a technical success rate and clinical success rate of 100% for transcatheter embolization using NBCA as was seen by Izaki et al, ( n = 12),[3] Madhusudhan et al, ( n = 31),[6] Won et al, ( n = 10)[14] in their studies on use of NBCA for embolization of visceral artery pseudoaneurysms. Song et al,[2] reported 92.3% (12 of 13 patients) technical success rate for transcatheter embolization of GI arterial, splenic artery, and hepatic arterial pseudoaneurysms using NBCA.…”
Section: Discussionsupporting
confidence: 72%
“…Madhusudhan et al,[6] reported 9.7% recurrences (3 out of 31 patients) within 30 days of transcatheter embolization which were managed by repeat embolization. Song et al,[2] Izaki et al,[3] and Won et al,[14] reported no recurrences. No recurrence of bleeding was seen in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In further comparison of these liquid embolics, NBCA has a very short working time due to rapid polymerization upon contact with ionic fluid ( i.e. blood) and can adhere to any material including vessel walls proximal to the intended target, and even the delivery system itself [77]. This can lead to permanent catheter occlusion requiring replacement of the delivery system and increasing procedure times, or even adherence of the catheter itself to the vessel wall.…”
Section: Commercially Available Materialsmentioning
confidence: 99%
“…Regarding embolization, metallic coils are used most often, while N-butyl-1,2-cyanoacrylate is rarely used because of handling difficulty and concerns regarding potentially fatal complications related to ischemic injury. However, N-butyl-1,2-cyanoacrylate has benefits if the vessels are too small or too tortuous to reach the aneurysm and keep stable catheter positioning, both of which are essential for coil embolization [10]. In this case, since the artery was too tortuous, we selected angiographic embolization with the mixture of N-butyl-1,2-cyanoacrylate and lipiodol as treatment and had successful results.…”
Section: Discussionmentioning
confidence: 99%